Effect of re-growth age in the content of secondary metabolites from Neonotonia wightii in the Valle del Cauto, Cuba - Verdecia, D.; Herrera, Rafael Segundo; Ram?rez, J. L.; Leonard, I.; Bodas, R.; Prieto, N.; Andr?s, S.; Girald?z, F. J.; Gonz?lez, J. S.; Arceo, Y.; Paumier, M.; ?lvarez, Y.; et al. (Cuban Journal of Agricultural Science, 2014)
The effect of regrowth age (30, 45, 60, 75 and 90 d) in the content of secondary metabolites from Neonotonia wightii was evaluated through a random blocks design, with six replications. The experiment took place from January to March (dry season) and from May to July (rainy season), in a carbonated brown soil, without irrigation and fertilization. Total tannins, total phenols, total condensed tannins, total mixed condensed tannins, free condensed tannins, flavonoids, saponins, alkaloids, triterpenes and steroids increased (P < 0.05) with age and the highest values were obtained at 90 d (5.24; 10.07; 77.67; 76.72; 0.95; 3.29; 0.53; 0.30; 8.58 and 0.63 g/kg DM during May-June-July and 3.12; 8.24; 96.64; 94.68; 1.96; 3.99; 0.52; 0.30; 8.51 and 0.69 g/kg DM during January-February-March, respectively). It can be concluded that regrowth age and climatic factors had a marked effect on the concentration of secondary metabolites. It was demonstrated that while the plant was maturing, the tenors of secondary metabolites increased. Only total condensed tannins and total mixed condensed tannins surpassed the limits in which the ruminant fermentation could be affected. It is recommended not to use this plant with an regrowth age higher than 75 d old. A similar study is suggested to be conducted with this and other legumes, in different environmental conditions, and to determine the relation between these metabolites and the digestibility and intake of these plants. Key words: legumes, maturity stage, tannins, flavonoids, saponins, alkaloids